The German and Italian government bond markets: The role of banks versus non-banks - Puriya Abbassi; Michele Leonardo Bianchi; Daniela Della Gatta; Raffaele Gallo; Hanna Gohlke; Daniel Krause; Arianna Miglietta; Luca Moller; Jens Orben; Onofrio Panzarino; Dario Ruzzi; Willy Scherrieble; et al. (Deutsche Bundesbank, 2024)
Government bond markets play a critical role in the smooth functioning of the financial system, in the conduct and transmission of monetary policy and in the economy as a whole. Maintaining resilient government bond markets is fundamental for policymakers and authorities. This note examines the German and Italian government bond markets, with a special focus on liquidity and on the role played by banks vs. non-banks. To this end, the holding and market structure of the German and Italian government bond markets are analysed at the granular sectoral level. We also look at the trading activities of various market participants in the repo and futures market. This comprehensive analysis enhances the understanding of government bond market dynamics, investor behaviour, and liquidity, providing insights for policymakers and market participants.
Keywords: G10; G21; G23; 330; government bonds; repo; futures; market structure; banks; non-bank financial intermediaries; financial stability